2008
DOI: 10.1021/jm800079s
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Series of Potent and Selective Ketone Histone Deacetylase Inhibitors with Antitumor Activity in Vivo

Abstract: Histone deacetylase (HDAC) inhibitors offer a promising strategy for cancer therapy, and the first generation HDAC inhibitors are currently in the clinic. Entirely novel ketone HDAC inhibitors have been developed from the cyclic tetrapeptide apicidin. These compounds show class I subtype selectivity and levels of cellular activity comparable to clinical candidates. A representative example has demonstrated tumor growth inhibition in a human colon HCT-116 carcinoma xenograft model comparable to known inhibitors. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…[6][7][8][9][10] A number of approaches to the synthesis of Aoda 1 have been adopted, including the use of chiral pool starting materials, 9,[11][12][13][14] and the use of chiral auxiliary groups. [15][16][17][18] Of most direct relevance to the topic of this paper is the report on the use of radical addition of chiral non-racemic amino acid fragments to enones. 12 However, there is as yet no general approach to a range of simple analogues of 8-oxo-2-aminodecanoic acid in which the position of the ketone and the length of the side-chain can be straightforwardly varied.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] A number of approaches to the synthesis of Aoda 1 have been adopted, including the use of chiral pool starting materials, 9,[11][12][13][14] and the use of chiral auxiliary groups. [15][16][17][18] Of most direct relevance to the topic of this paper is the report on the use of radical addition of chiral non-racemic amino acid fragments to enones. 12 However, there is as yet no general approach to a range of simple analogues of 8-oxo-2-aminodecanoic acid in which the position of the ketone and the length of the side-chain can be straightforwardly varied.…”
Section: Introductionmentioning
confidence: 99%
“…From the study of Jones et al (52,53), we found a potent HDAC inhibitor with a methylketone ZBG. Based on their study, researchers tried to find if compounds with the sulfamide at the e-nitrogen are potent and selective for HDAC6 inhibition.…”
Section: Sulfamidesmentioning
confidence: 95%
“…HDACs 4, 5, 7 are not inhibited by 13 at levels as high as 10 mM. The 4-phenylimidazole derivative displayed submicromolar IC 50 antiproliferation activity against cervical, colon and kidney cell lines [84]. This compound also inhibits tumor growth in a xenograft model.…”
Section: Ink4amentioning
confidence: 97%
“…Apicidin shows antiproliferative activity against a variety of cancer cell lines by a mechanism that appears to involve induction of the p21 WAF1/Cip1 gene [72]. Recently, nonpeptidic analogs of apicidin were developed to improve potency and selectivity in HDAC inhibition [83,84]. A 4-phenylimidazole derivative (13) with a methyl ketone zinc-binding group selectively inhibits HDACs 1, 2, 3 (IC 50 values $100 nM) and HDAC 6 (IC 50 $300 nM).…”
Section: Ink4amentioning
confidence: 99%